Geogenic factors affecting the selenium(IV) distribution in sediments from Madeira River Basin, Brazil - Da Costa Neto, A.; Bonotto, Daniel Marcos [UNESP]; Mesquita, F. L A (WITPRESS LTD., 2003)
This investigation was carried out at the Madeira River basin, located in the state of Rondônia, Brazilian Amazon. Sediments from Madeira River between Teotônio and Santo Antônio waterfalls along 25 km upstream from Porto Velho, the capital of Rondônia state, and from nine lakes located around Porto Velho municipality were chemically analyzed for Se (IV) in order to evaluate the main factors affecting the Se(IV) distribution in the environment, Selenite ion was chosen to investigate the selenium behavior in the area, because acid conditions are dominant there. The importance of clays, iron oxides, organic matter and minor refractory minerals was considered in order to explain most of the obtained data.
Keywords: Enamels; Environmental impact; Lakes; Membranes; Nutrition; Pigments; Redox reactions; Refractory materials; Sediments; Selenium compounds; Toxicity; Wastewater; Acid conditions; Geogenic factors; Madeira River basin; waterfalls; River basin projects